Rethinking Human Development: Contributions of Mahbub Ul Haq, Amartya Sen, and Umer Chapra to Conventional and Islamic Indices - Jannah, Nurul; Tarigan, Azhari Akmal; Helmi, Muhammad; Harahap, Fasthabiqul Ambiya (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
This study examines the evolution of human development measurements by comparing the Human Development Index (HDI) and the Islamic Human Development Index (IHDI). The HDI, developed by Mahbub Ul Haq and Amartya Sen, assesses life expectancy, education, and income but has been criticized for overlooking ethical and spiritual dimensions. In response, Umer Chapra proposed the IHDI, which integrates *maqasid al-shari'ah* (objectives of Islamic law), emphasizing religion, intellect, life, lineage, and wealth. Using a descriptive qualitative approach, this study analyzes literature on the HDI and IHDI, assessing their conceptual frameworks and applications. Findings indicate that while the HDI provides a broad measure of well-being, the IHDI offers a more holistic approach by incorporating ethical and spiritual values, though its implementation remains underdeveloped. The study highlights the growing need for development indices that reflect both material and non-material aspects of well-being, as human progress extends beyond economic indicators. To achieve a comprehensive measure of development, future research should explore the practical application of the IHDI, ensuring it effectively captures the multidimensional nature of human flourishing.